2001
DOI: 10.1021/ja010155m
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Diblock Dendrimers:  Synthesis and Incorporation in Langmuir and Langmuir−Blodgett Films

Abstract: A new dendron with peripheral long alkyl chains and containing five C(60) units in the branching shell has been prepared and attached to a Fréchet-type dendron functionalized with ethylene glycol chains. The peripheral substitution of the resulting globular dendrimer with hydrophobic chains on one hemisphere and hydrophilic groups on the other provides the perfect hydrophobic/hydrophilic balance allowing the formation of stable Langmuir films. Furthermore, a perfect reversibility has been observed in successiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 52 publications
2
61
0
Order By: Relevance
“…Working on [60]fullerene bisadducts, Nierengarten and coworkers have shown that encapsulation of the carbon sphere in a cyclic addend surrounded by either long alkyl chains [42,43] or cholesterol subunits [44] is a method of choice for obtaining stable and reversible monomolecular thin films, easily transferred onto solid substrates in order to prepare high quality LB multilayers. Using an alternative approach to the previous studies, the same group demonstrated that the fullerene can be attached into the branching shell of a dendritic [45] or diblock dendritic [46,47] structure. In this case, the C 60 units are buried in the middle of the dendrimer which provides an insulating layer around them, thus preventing the irreversible three-dimensional aggregation resulting from fullerene-fullerene interactions (for example, see: [48,49]).…”
Section: Thin Films As Induced Organization Of [60]fullerene Hexakisamentioning
confidence: 99%
“…Working on [60]fullerene bisadducts, Nierengarten and coworkers have shown that encapsulation of the carbon sphere in a cyclic addend surrounded by either long alkyl chains [42,43] or cholesterol subunits [44] is a method of choice for obtaining stable and reversible monomolecular thin films, easily transferred onto solid substrates in order to prepare high quality LB multilayers. Using an alternative approach to the previous studies, the same group demonstrated that the fullerene can be attached into the branching shell of a dendritic [45] or diblock dendritic [46,47] structure. In this case, the C 60 units are buried in the middle of the dendrimer which provides an insulating layer around them, thus preventing the irreversible three-dimensional aggregation resulting from fullerene-fullerene interactions (for example, see: [48,49]).…”
Section: Thin Films As Induced Organization Of [60]fullerene Hexakisamentioning
confidence: 99%
“…In connection with the before described fullerene dendrons that have been employed in Langmuir or LB films, the same group designed a more sophisticated system of amphiphilic character [31]. Carboxylic acid 28 containing five fullerene moieties was thus coupled to a polyethylene glycol terminated Fréchet-type dendron of third generation to give amphiphilic fullerene-rich dendrimer 38 ( Figure 3).…”
Section: Dendrimersmentioning
confidence: 99%
“…Therefore, the attachment of these dendrons on a core for the preparation of fullerene-rich macromolecules appears difficult. This prompted us to design new dendritic branches containing an increased number of solubilizing groups [51]. The synthesis of this fullerodendron is depicted in Fig.…”
Section: Dendrons Containing a C 60 Sphere At Each Branching Unitmentioning
confidence: 99%